نظام العقوبات النبویۃ حالۃ التغلب علی الأعداءعقوبۃالإعدام یومی فتح مکۃ وبنی قریظۃ: The system of prophetic punishments overcoming enemies With special reference to the death penalty on the conquest of Makkah and Banu Qurayza - Dr. Anas Sarmini (Seerat Studies, 2023)
Being the life of the Holy Prophet (SAW) a role model for us in every sphere of life, it is mandatory to extract principles from his life, but the principles must be extracted in the light of two main principles to extract the correct conclusions: i-A deep research-based study of the Ahadith of the Prophet Muhammad (SAW). ii- Deep understanding of the science of jurisprudence. In the events of the biography of the holy Prophet (SAW), two events are more considerable, the case of the fight of Bani-Quraizah and the conquest of Makkah, because it is the famous exploration that the holy Prophet (SAW) granted a common forgiveness to the prisoners and enemies during the conquest of Makkah, whereas in the case of Bani-Quraizah , it is a famous verdict that all the prisoners and enemies were let to meet their end. “Whether every famous verdict could be taken as granted?” This is the question which the researcher has tried to answer comprehensively. The article presents a critical and analytical appraisal about these two historical events.